DEVELOPMENT OF ECLIPSE CROSSWORD ASSISTED CROSSWORD LEARNING MEDIA IN DIGESTIVE SYSTEM MATERIALS IN JUNIOR HIGH SCHOOL - Diana Rohma Wati; Andi Suhardi (INSECTA: Integrative Science Education and Teaching Activity Journal, 2022)
This study aims to produce a product of learning media, namely crossword puzzles assisted by eclipse crossword on the Digestive System material conducted at MTs Walisongo Wonokerto Lumajang. Operationally, the objectives are broken down into two, namely describing the validity of the eclipse crossword-assisted learning media on the digestive system material and describing the students' responses to the eclipse crossword-assisted learning media on the digestive system material. This type of research is a research and development (Research and Development) Borg and Gall model using 7 steps, namely: Research and Information Collection, Planning, Develop Preliminary form of Product, Preliminary Field Testing, Main Product Revision, Main Field Testing, and Operational Product Revision . Based on the results of the validation analysis from material experts, media experts and practitioner experts, it shows that the percentage of the validity of each assessment is 96.5%, 94.5% and 95% with an average value from the experts which is 95% which these results include in the "Very Valid" category, while the results of the analysis of the limited-scale trial and large-scale trials resulted in a score of 87% and 88% which resulted in an average of 88%, this value was included in the "Very Interesting" criteria.